Actividad antioxidante in vitro de hojas, tallo y fruto de Senna occidentalis - Flores Vela, Liz Karina (2024)
Objective: To determine the antioxidant activity of the leaves, stems, and fruits of Senna occidentalis. Methodology: The study population included all S. occidentalis (retamilla) shrubs present at km 04 of the Iquitos – Nauta road, Loreto region. The organs of the studied species were collected by convenience and georeferenced (3°57'46" S, 73°24'54" W). Methanolic extracts of these samples were prepared to evaluate antioxidant activity using the DPPH method, tested at concentrations of 1, 10, 25, and 50 mg/mL. Results: Methanolic extracts of the leaves, stems, and fruits of S. occidentalis showed an inhibition percentage of less than 50% and an IC50 greater than 50 mg/mL. Conclusion: All methanolic extracts of S. occidentalis did not exhibit antioxidant activity at the evaluated concentrations.